2015
DOI: 10.1007/s13246-015-0361-6
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex-specific relationships between blood pressure variability and carotid intima-media thickness

Abstract: This study evaluated the association between carotid intima-media thickness (IMT) and 24 h ambulatory blood pressure variability (BPV) in 150 subjects. The subjects were divided into different age groups and gender groups. We found that for the subjects aged less than 45 years, 24 h and daytime diastolic BPV were associated with the increased IMT (r = 0.525, P = 0.018; r = 0.507, P = 0.022). For the middle aged people (46-55 years), daytime (r = 0.377, P = 0.014) and 24 h systolic BPV (r = 0.366, P = 0.017) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Various preceding studies examined the possible gender difference in the association between metabolic risk factors and IMT. [27][28][29][30][31][32] This point is still under debate and is clinically important for the risk assessment of the general population from the perspective of preventive cardiology. Further study is required to clarify the significance of WC for the prediction of preclinical atherosclerosis in women.…”
Section: Discussionmentioning
confidence: 99%
“…Various preceding studies examined the possible gender difference in the association between metabolic risk factors and IMT. [27][28][29][30][31][32] This point is still under debate and is clinically important for the risk assessment of the general population from the perspective of preventive cardiology. Further study is required to clarify the significance of WC for the prediction of preclinical atherosclerosis in women.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were also supported by some cross-sectional studies and longitudinal studies. Part of studies suggested that BPV was associated with carotid atherosclerosis [22], stroke [23, 24], and vascular events [25]. A 10-year follow-up study showed that higher long-term SBP variability may be a risk factor for arterial stiffness progression independent of mean BP, as a result of that, higher systolic blood pressure (SBP) variability may reduce bioavailability of nitric oxide and increase vascular smooth muscle cell proliferation [26].…”
Section: Discussionmentioning
confidence: 99%
“…And a United Kingdom study of more than 20,000 large-scale population studies with a follow-up of 29 years showed a brief higher reading of diastolic blood pressure (indicating higher blood pressure variability), cardiovascular disease, and all-cause mortality were closely related only to women, not men [19]. However, a recent study showed that 24 h SBPV was an independent factor in assessing carotid IMT in male, but not in female [22]. The pathophysiologic mechanisms were poorly defined, although many hypotheses were proposed with the hormonal component being the prevailing [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral arterial remodeling disrupted hemodynamics and caused hypoperfusion, leading to increased production and decreased clearance of amyloid-beta [ 91 ]. The relationships between IMT and 24-h SBPV were more evident in male than female participants, indicating that 24-h ARV of SBPV was the independent factor for increased carotid IMT in males but not in females [ 92 ]. However, in another larger clinical study of 957 healthy individuals, 24-h weighted SD of BPV is related to arterial stiffness in middle-aged and older adults and more correlated in females [ 93 ].…”
Section: Potential Mechanisms Underlying the Relationship Between Blo...mentioning
confidence: 99%